2021
DOI: 10.1097/cce.0000000000000386
|View full text |Cite
|
Sign up to set email alerts
|

The Modified Early Warning Score: A Useful Marker of Neurological Worsening but Unreliable Predictor of Sepsis in the Neurocritically Ill—A Retrospective Cohort Study

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…PEWS was studied in a limited number of pediatric patients in various subgroups. 21,23,24 Limited literature reviews 8,10 were also performed amongst adults, which revealed heterogeneity in the predictive performance of the early warning score across diseases, despite the fact that the current study demonstrated superior performance across all disease subgroups (ROC 0.843 -0.972). Alhmoud et al 10 conducted a large systematic review of early warning scores in adults and revealed that while stroke, cardiac, and renal diseases had the best predictive performance, enhanced accuracy was demonstrated in gastrointestinal, hematologic and respiratory diseases (ROC 0.93 -0.972), despite lowest in neurological disease in this study.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…PEWS was studied in a limited number of pediatric patients in various subgroups. 21,23,24 Limited literature reviews 8,10 were also performed amongst adults, which revealed heterogeneity in the predictive performance of the early warning score across diseases, despite the fact that the current study demonstrated superior performance across all disease subgroups (ROC 0.843 -0.972). Alhmoud et al 10 conducted a large systematic review of early warning scores in adults and revealed that while stroke, cardiac, and renal diseases had the best predictive performance, enhanced accuracy was demonstrated in gastrointestinal, hematologic and respiratory diseases (ROC 0.93 -0.972), despite lowest in neurological disease in this study.…”
Section: Discussionmentioning
confidence: 66%
“…PEWS was studied in a limited number of pediatric patients in various subgroups. 21,23,24 Limited literature reviews 8,10 were also performed amongst adults, which Neurological disease evaluation in children can be challenging because it requires specific critical alarms such as irritability, and training for abnormal neurological signs detection. Modifications to the clinical item and scoring system in the PEWS, as well as intensive training for nurses, may be necessary to increase predictability when using the PEWS.…”
Section: Discussionmentioning
confidence: 99%
“…A small Polish study also showed that the MEWS predicted a severe course of SARS-CoV-2 infection [ 47 ]. The MEWS, which appears to be reliable and easy to assess, was found to be useful in predicting neurological worsening in a cohort of more than 7000 neurocritically ill patients with COVID-19 [ 48 ]. However, a recent Indian study showed that not many rating scales, including the MEWS, were found to be useful in identifying patients with COVID-19 who are at risk for clinical worsening [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…This decrease was observed at a time when leukocyte and neutrophil counts are typically elevated. This observation is especially significant since ( 1 ) we analyzed whole blood (rather than PBMC), and ( 2 ) it is therefore likely that a portion of these scant PMN-MDSCs are mature neutrophils, since CD11b + CD15 + CD14 − CD33 +/low CD66b + markers enrich for neutrophils at all maturation stages ( 10 ). High PMN-MDSCs within the first week of sepsis onset have been recently associated with secondary infections, while M-MDSCs appear to be more abundant in sepsis survivors ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…This prospective, observational trial was performed on critically ill, adult patients and healthy control volunteers, between 11/2021 and 6/2022. Hospitalized patients were screened for potential sepsis, based on Modified Early Warning Score-Sepsis (MEWS-Sepsis) Recognition Score ( 10 12 ), by using a computational algorithm executed twice daily. Two investigators then independently assessed each identified patient for study inclusion according to Sepsis-3 criteria ( 4 ).…”
Section: Methodsmentioning
confidence: 99%